Comparing Intensive Trauma-Focused Treatment Outcome on PTSD Symptom Severity in Older and Younger Adults - Ellen M. J. Gielkens (Journal of Clinical Medicine, 2021)
Objective: To examine the treatment outcome of an intensive trauma-focused treatment program for post-traumatic stress disorder (PTSD) in older and younger adults. Methods: A non-randomized outcome study was conducted with 62 consecutively admitted older PTSD patients (60–78 years) and 62 younger PTSD patients (19–58 years), matched on gender and availability of follow-up data. Patients participated in an intensive eight-day trauma-focused treatment program consisting of eye movement desensitization and reprocessing (EMDR), prolonged exposure (PE), physical activity, and group psycho-education. PTSD symptom severity (Clinician-Administered PTSD Scale-5 (CAPS-5)) was assessed, at pre- and post-treatment, and for a subsample (n = 31 older; n = 31 younger patients) at six-month follow-up. Results: A repeated-measures ANCOVA (centered CAPS pre-treatment score as covariate) indicated a significant decrease in CAPS-5-scores from pre- to post-treatment for the total sample (partial η2 = 0.808). The treatment outcome was not significantly different across age groups (partial η2 = 0.002). There were no significant differences in treatment response across age groups for the follow-up subsample (pre- to post-treatment partial η2 < 0.001; post-treatment to follow-up partial η2 = 0.006), and the large decrease in CAPS-5 scores from pre- to post-treatment (partial η2 = 0.76) was maintained at follow-up (partial η2 = 0.003). Conclusion: The results suggest that intensive trauma-focused treatment is applicable for older adults with PTSD with a large within-effect size comparable to younger participants. Further research on age-related features is needed to examine whether these results can be replicated in the oldest-old (>80).